Binary-induced spiral arms inside the disc cavity of AB Aurigae. Issue 2 (12th June 2020) - Poblete, Pedro P; Calcino, Josh; Cuello, Nicolás; Macías, Enrique; Ribas, Álvaro; Price, Daniel J; Cuadra, Jorge; Pinte, Christophe
ABSTRACT: In this work we demonstrate that the inner spiral structure observed in AB Aurigae can be created by a binary star orbiting inside the dust cavity. We find that a companion with a mass-ratio of 0.25, semimajor axis of 40 au, eccentricity of 0.5, and inclination of 90° produces gaseous spirals closely matching the ones observed in 12 CO (2-1) line emission. Based on dust dynamics in circumbinary discs (Poblete, Cuello & Cuadra 2019 ), we constrain the inclination of the binary with respect to the circumbinary disc to range between 60° and 90°. We predict that the stellar companion is located roughly 0.18 arcsec from the central star towards the east-southeast, above the plane of the disc. Should this companion be detected in the near future, our model indicates that it should be moving away from the primary star at a rate of 6 mas yr −1 on the plane of the sky. Since our companion is inclined, we also predict that the spiral structure will appear to change with time, and not simply corotate with the companion.